2022
DOI: 10.1111/jcpe.13627
|View full text |Cite
|
Sign up to set email alerts
|

Modified minimally invasive surgical technique in human intrabony defects with or without regenerative materials—10‐year follow‐up of a randomized clinical trial: Tooth retention, periodontitis recurrence, and costs

Abstract: Aim The modified minimally invasive surgical technique (M‐MIST) optimizes wound stability in the treatment of intrabony defects. Short‐term observations show similar results as with flap alone or adjunctive regenerative materials. This study aims to compare the stability of the long‐term outcomes, complication‐free survival, and costs of the three treatment options. Materials and Methods Forty‐five intrabony defects in 45 patients were randomized to M‐MIST alone (N = 15), combined with enamel matrix derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…Relying on the results of the present analysis, we may assume that both 6‐month residual PD and 6‐month CAL change may substantially influence the long‐term stability of the regenerative outcomes. In this respect, the presence/absence of a residual pocket represented the main difference between COM1/COM2 and COM4, further corroborating the current evidence on the predictive value of residual PD for disease progression/recurrence following active periodontal therapy, in general, 40–42 and regenerative procedures, in particular 11,13,43 . Moreover, defects categorized in COM3 showed an intermediate behavior between COM1/2 and COM4 in terms of proportion of stable defects at 4 years and need for surgical reintervention, thus suggesting the importance of a relevant CAL gain in mitigating the detrimental effect of the residual pocket on the long‐term stability of the regenerative outcome.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Relying on the results of the present analysis, we may assume that both 6‐month residual PD and 6‐month CAL change may substantially influence the long‐term stability of the regenerative outcomes. In this respect, the presence/absence of a residual pocket represented the main difference between COM1/COM2 and COM4, further corroborating the current evidence on the predictive value of residual PD for disease progression/recurrence following active periodontal therapy, in general, 40–42 and regenerative procedures, in particular 11,13,43 . Moreover, defects categorized in COM3 showed an intermediate behavior between COM1/2 and COM4 in terms of proportion of stable defects at 4 years and need for surgical reintervention, thus suggesting the importance of a relevant CAL gain in mitigating the detrimental effect of the residual pocket on the long‐term stability of the regenerative outcome.…”
Section: Discussionsupporting
confidence: 80%
“…However, longterm data stemming from well-designed RCTs on different regenerative modalities seem to suggest that the stability of periodontal condition can be maintained irrespectively of the regenerative device used, provided the patients are enrolled in a stringent SPC regimen. 12,13,15 High prevalence of periodontal stability between 6 months to 4 years and 100% tooth survival were observed among defects in COM1 group. All cases in this group did not need surgical retreatment during the observation period.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Data from three studies with a follow-up ranging from 2 to 5 years indicated a substantial risk varying from 8% to 44%. Corresponding data on severely compromised teeth followed over 10 years after periodontal therapy (Cortellini et al, 2020(Cortellini et al, , 2022 indicated lower risk of recurrence as expressed by >7 mean years of complication-free survival. In contrast to disease recurrence, the outcome "implant loss" was consistently reported.…”
Section: Teughels Et Al (Systematic Reviews Prepared For the XVIII Eu...mentioning
confidence: 96%
“…Modern periodontal therapy is rich with treatment approaches, regenerative in particular, that may help clinicians to preserve more teeth during the active phase, as highlighted by the Guidelines of the European Federation of Periodontology (Sanz et al, 2020). Regenerative surgery reportedly improves the long‐term prognosis of teeth with furcation involvement (Huynh‐Ba et al, 2009; Dannewitz et al, 2016; Nibali et al, 2020), teeth with furcation involvement associated with deep intrabony defects (Cortellini, Cortellini, & Tonetti, 2020; Cortellini, Stalpers, et al, 2020), teeth with deep intrabony defects (Cortellini et al, 2017; Nibali et al, 2020; Cortellini et al, 2022), and even teeth with a baseline “hopeless” prognosis (Cortellini et al, 2011; Cortellini, Cortellini, & Tonetti, 2020; Cortellini, Stalpers, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%